EVALUATION THE PERFORMANCE OF DEVELOPED MOLDBOARD PLOW AND It’s EFFECT ON SOME PERFORMANCE INDICATORS OF THE MECHINERY UNIT - & et al., Al-Alabiedi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A field experiment was conducted in Alshakha area in Alexandria region in 2013, which lies 50 km south of Baghdad province, in order to evaluate the performance of the modified moldboard plow and its effect on some technical indicators of machinery unit percentage of slip, pulling power practice productivity and the size of disturbed soil. complete randomized block design and split plot design was used tillage depth included 15, 20 and 25 cm, levels with machinery speed included 2.6 and 3.6 km / h which represented sub plot ,were shaded in this study. The result were shoved that the lowest percentage of slippage and less pulling power and less a matter of the size of the soil and the highest productivity process when tillage depth of 15 cm, was obtained to less percentage slip and less pulling power when tug speed of 2.6 km / h. The overlap between the plowing depth of 15 cm and tug speed 2.6 km / h to obtain the lowest percentage of slippage and less strength and less drag size of the soil raised.